Stabilitas emulsi kopolimer S-GMA (stirena – glisidil metakrilat) - Isananto Winursito (Majalah Kulit, Karet, dan Plastik, 1992)
Epoxy groups in glycidyl methacrylate (GMA) units have been available for the reaction with amine of proteins or other biological active substrates to prepare biomaterials and hybrid devices. Soap-soap copolymerization of GMA with styrene (S) result the formation of stable latex. Hydrolysis of epoxy groups in copolymer particles increased emulsion stability. The effect of pH, temperature and reaction time in the hydrolysis of S-GMA copolymer have been investigated.   INTISARI Gugus epoksi dalam glisidil matakrilat (GMA) dapat digunakan untuk mengikat gugus amina pada protein atau substrat aktif biologi untuk menyiapan suatu biomaterial dan peralatan hibrida. Kopolimerisasi GMA dengan stirena (S) tanpa menggunakan pengemulsi dapat menghasilkan la teks yang stabil. Hidrolisa gugus epoksi dalam partikel kompolimer ini menaikkan stabilitas emulsi. Pada penelitian ini telah dipelajari pengaruh pH, suhu dan waktu reaksi dalam hidrolisa kopolimer S-GMA.